2018
DOI: 10.1088/1361-6579/aaa924
|View full text |Cite
|
Sign up to set email alerts
|

Detection of thoracic vascular structures by electrical impedance tomography: a systematic assessment of prominence peak analysis of impedance changes

Abstract: It is possible to detect the descending aorta at different thoracic levels by EIT using an intra-aortic bolus of hypertonic saline. No significant differences in the position of the descending aorta on EIT images compared to CT images were obtained for both EIT belts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From these boundary voltage measurements, it is possible to estimate the internal conductivity distribution of the body. Medical applications include imaging of brain activity [1], monitoring of lung function [2]- [4], and detection of breast cancer [5] and thoracic vascular structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…From these boundary voltage measurements, it is possible to estimate the internal conductivity distribution of the body. Medical applications include imaging of brain activity [1], monitoring of lung function [2]- [4], and detection of breast cancer [5] and thoracic vascular structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…EIT biological applications involved multiple tissue and organ such as the brain [ 23 ], breast [ 24 ], prostate [ 25 ], bladder [ 26 ], stomach [ 27 ], and blood vessels [ 28 ], etc., consistent with our result that keywords were clustered into 18 topics. The cluster intensity and the specific topic analysis showed that applications in brain anatomical structure, breast cancer, and hemodynamics were hot topics over time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lung imaging, cardiac and vascular imaging within the thorax represents a unique, but challenging opportunity for EIT. Braun et al (2018) highlights the challenges in monitoring stroke volume and pulmonary arterial pressure and Wodack et al (2018) assesses the potential of detecting thoracic vascularity using EIT. EIT-based applications in neural and intracranial imaging continue to be explored.…”
Section: Exploration Of Clinical Applicationsmentioning
confidence: 99%